Plant kinetochore complex: composition, function, and regulation - Xie, Yuqian; Wang, Mingliang; Mo, Beixin; Liang, Chao (Frontiers in Plant Science, 2024)
The kinetochore complex, an important protein assembly situated on the centromere, plays a pivotal role in chromosome segregation during cell division. Like in animals and fungi, the plant kinetochore complex is important for maintaining chromosome stability, regulating microtubule attachment, executing error correction mechanisms, and participating in signaling pathways to ensure accurate chromosome segregation. This review summarizes the composition, function, and regulation of the plant kinetochore complex, emphasizing the interactions of kinetochore proteins with centromeric DNAs (cenDNAs) and RNAs (cenRNAs). Additionally, the applications of the centromeric histone H3 variant (the core kinetochore protein CENH3, first identified as CENP-A in mammals) in the generation of ploidy-variable plants and synthesis of plant artificial chromosomes (PACs) are discussed. The review serves as a comprehensive roadmap for researchers delving into plant kinetochore exploration, highlighting the potential of kinetochore proteins in driving technological innovations in synthetic genomics and plant biotechnology.